Candida auris Identification and Rapid Antifungal Susceptibility Testing Against Echinocandins by MALDI-TOF MS - Vatanshenassan, Mansoureh; Boekhout, Teun; Meis, Jacques F.; Berman, Judith; Chowdhary, Anuradha; Ben-Ami, Ronen; Sparbier, Katrin; Kostrzewa, Markus (Frontiers in Cellular and Infection Microbiology, 2019)
Candida auris was first reported in an ear swab from Japan in 2009; it then promptly spread over five continents and turned into a global nosocomial problem. The main challenges faced by many researchers are the mis-identification by conventional methods in clinical laboratories and failure in treatment. About 90% of C. auris strains are intrinsically resistant to fluconazole (FLU), and it is developing resistance to multiple classes of available antifungals. Echinocandins are the most potent class of antifungals against C. auris; however, reduced susceptibility to one or many echinocandin drugs has been recently observed. Thus, the main issues addressed in this paper are the fast and accurate identification of C. auris derived from Sabouraud dextrose agar and blood culture bottles as well as the rapid antifungal susceptibility test by MALDI-TOF MS. This study successfully identified all clinical isolates of C. auris (n= 50) by MALDI-TOF MS, with an average log score of ≥ 2. An accuracy of 100% was found on both agar plate and blood culture bottles. MALDI Biotyper antibiotic susceptibility test-rapid assay (MBT ASTRA) was used for rapid antifungal susceptibility testing (AFST). A comparison between MBT ASTRA and the Clinical and Laboratory Standards Institute guidelines (CLSI) detected a sensitivity and specificity of 100% and 98% for anidulafungin, and 100% and 95.5% for micafungin, respectively. A categorical agreement of 98% and 96% was calculated for the two methods. For caspofungin, sensitivity and specificity of 100% and 73% were found, respectively, with a categorical agreement of 82%. MBT ASTRA has the great potential to detect C. auris isolates resistant against echinocandin antifungals within 6h, which makes it a promising candidate for AFST in clinical laboratories in the future.